Answer:
Explanation:
The graph is a straight line graph. The equation of a straight line can be represented in the slope-intercept form, y = mx + c
Where c = intercept
Slope, m =change in value of y on the vertical axis / change in value of x on the horizontal axis
change in the value of y = y2 - y1
Change in value of x = x2 -x1
y2 = final value of y
y 1 = initial value of y
x2 = final value of x
x1 = initial value of x
From the graph,
y2 = - 5
y1 = 1
x 2 = 1
x1 = -2
Slope = (- 5 -1)/(1 - -2) = -6/3 = -2
m = -2
The equation becomes
y = -2x + c
We need to determine c. Let us use (1,-5)
-5 = -2 ×1 + c
-5 = -2 + c
c = -5 + 2 = -3
The equation is
y = -2x -3